Association between Puberty, Bulimia Nervosa and Depression (Bangladesh Journal of Medical Science, 2015)
Background: Anorexia Nervosa (AN) and Bulimia Nervosa (BN) are diseases characterized by an eating disorder, distorted weight regulation and distorted perception of ones body. In the period of puberty adolescents are becoming increasingly vulnerable to eating disorders. Objective: The target of this study was to examine the prevalence of possible eating disorder (bulimia nervosa) and depression in the period of puberty. Methods: The study group included 233 students from secondary schools, of whom 128 were boys and 105 girls, with an average mean age of 14 years. The Eating Attitude Test (EAT-26) and Childrens Depression Inventory (CDI) were applied to the entire study population. Also we calculate the Body Mass Index (BMI); a parameter defines as the ratio of human body weight and height. Results: According to the EAT, 73 (32%) students had a EAT score indicating a possible diagnosis of bulimia nervosa. The authors observed statistically significant increased frequency of depressive thoughts in the study group. 188 (81%) students had emotional symptoms of depression Correlation results indicated that depressed mood scores positively correlated with bulimia scores. Conclusions: We observed high prevalence of bulimia nervosa and depression in the period of puberty.Bangladesh Journal of Medical Science Vol.14(4) 2015 p.327-330